Blue economy risks and challenges in Ghana: a systematic literature review - Ansah, John Windie; Oduro, Georgina Yaa (Frontiers in Marine Science, 2025)
Although blue economy has become an integral part of national efforts towards promoting economic growth, the activities and policies have been notable sources of livelihood and survival risks in Ghana. It is, however, unclear how these unpacked risks have been anchored on a particular blue economy effort and the variety of risks a blue economy effort could produces. Through a systematic review of the literature, this study explores the sources of the blue economy risks and challenges as well as account for each blue risk and challenge as derivative of blue economy efforts. The results of the review demonstrate a myriad of risks and challenges in Ghana’s blue economy which are developmental, natural and relational ranging from livelihoods vulnerabilities, insecurity, environmental pollution, overexploitation of fish resources, conflicts as well as dispossession and displacement. While the results reveal that each of the blue economy risks is a product of multiple industrial activities, the review also makes it clear that a single blue economy activity or policy could produce multiple blue economy risks and challenges. This creates a complex matrix of blue economy risks in terms of nature and sources. The results suggest that researchers have frequently displayed widespread and diverse blue economy risks which occur through varying processes from selected industry-related activities and rarely from enacted and implemented policies. As efforts towards the development of an omnibus blue economy policy in Ghana are underway, we regard them as prerequisites of a mixed method investigation into the risks embedded in all blue economy activities and policies in Ghana in a manner that it can lead to incomparably superior results across all studies.